Study on the High-Temperature Corrosion Behavior of Cr3C2/Cr2AlC MAX Phase Composite Coatings on Stainless Steel Surfaces in Molten Sodium Polysulfide - CUI Xingcheng, REN Yanjie, XIAO Biao, LI Yanhua, CHEN Jian, ZHOU Libo, QIU Wei, HUANG Weiying, NIU Yan (Cailiao Baohu)
In order to address the issue of thermal expansion coefficient mismatch between Cr3C2 coatings and 304 stainless steel, and to enhance the corrosion resistance of 304 stainless steel, two different structural Cr3C2/Cr2AlC MAX composite coatings were prepared on the surface of 304 stainless steel using magnetron sputtering technology.The microstructure and phase composition of the coatings were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive spectroscopy (EDS) techniques.A comparative analysis was conducted on the corrosion resistance and behavior of Cr3C2/Cr2AlC MAX composite coatings with different structures in molten sodium polysulfide, as well as a single-layer Cr2AlC MAX coating.Results showed that the Cr3C2/Cr2AlC MAX composite coatings were dense and uniform, and were primarily composed of Cr3C2 and Cr2AlC MAX phases.After 120 h of corrosion, the corrosion rate of the Cr3C2/Cr2AlC MAX composite double-layer coating was measured at 0.03 mg/(m2∙h), while the corrosion rate of the Cr3C2/Cr2AlC MAX composite multilayer coating was recorded at 0.02 mg/(m2∙h),which was two orders of magnitude lower than that of the single-layer Cr2AlC MAX coating.Following corrosion in sodium polysulfide,a dense layer of Cr2S3 corrosion products was formed on the surfaces of both types of Cr3C2/Cr2AlC MAX composite coatings.After 120 h of corrosion,cracks were observed on the surface of the composite double-layer coating,which were attributed to thermal stress concentration leading to surface cracking.In contrast, the composite multilayer coating remained dense and defect-free even after prolonged exposure to corrosion, and was shown to demonstrate excellent corrosion resistance and stability in sodium polysulfide environments.